218k views
23 votes
Please add am explanation.

Please add am explanation.-example-1

1 Answer

3 votes

Answer:

5(k + 1) and 5k + 5

Explanation:

The easiest way to do this is to pick any number to substitute in for the variable k for ALL of the expressions, and find the expressions that equal the same as the first expression being compared.

For example, lets just make k equal 1 to make things easy. Plug 1 into k into the first expression. 2k + 2 + k + 3 + 2k → 2(1) + 2 + (1) + 3 + 2(1) = 10.

Now we do the same to the rest of the expressions and see which ones ALSO equal 10.

5(k + 1) → 5(1 + 1) = 10

5k + 5 → 5(1) + 5 = 10

5 + k^5 → 5 + (1)^5 = 6

5k^5 → 5(1)^5 = 5

User AutoBaker
by
4.6k points